¿Cómo transformar un elipsoide en un esferoide? Técnica quirúrgica para la corrección de la sinostosis sagital basada en un modelo geométrico - Morsucci, E.; Houssay, A.; Beninca, J.; Ferraro, Florencia; Ibáñez, M. (Revista Argentina de Neurocirugía, 2021)
INTRODUCTION: Sagittal synostosis is the most common craniosynostosis. There is still debate about which is the most appropriate surgical method for its treatment. This work presents a surgical technique based on a geometric model that answers the question: How to transform an ellipsoid body into a spheroid one?MATERIALS AND METHODS: A surgical technique is described as a method that allows modeling the skull of an infant with dolichocephalic conformation. A geometric model is developed, showing step by step how an ellipsoid figure is modified, improving its width / length ratio. Later, this model in "the map" is transferred to a 3-D model, being able to verify the change of shape. Finally, we present 8 cases of operated patients, showing that the theoretical model correlates with the "in vivo" model.RESULTS: 8 patients with this type of craniosynostosis, 6 boys and 2 girls, were operated on. The ages were from 2 to 7 months. An improvement in the cephalic index (CI) was verified in all of them, measured in the immediate postoperative period. The average CI prior to surgery was 0.67 SD = 0.021 and, for the same population in the postoperative period, it was 0.77 SD = 0.035. Student's t test for paired samples was 7.84, which gives a null hypothesis P
Keywords: scaphocephaly; sagittal synostosis; Cephalic Index